Identification for Development : Botswana - World Bank Group (World Bank, Washington, DC, 2017)
This report analyzes the Identity Management System of the Republic of Botswana with respect to 1) accessibility, 2) robustness, 3) integration and regulated access to data, and 4) legal frameworks and data protection, and documents the extent to which the legal and institutional framework and the human and physical infrastructures have facilitated the establishment, operationalization and management of identity management as a comprehensive system. Botswana has a single foundational Identity Management System which is a primary tool for public administration and governance as well as facilitation of service delivery to the public. It creates one identity per person pursuant to the current legal framework which is used several times by the person at various institutions to facilitate the individual’s access to services including social safety net programs, claiming of rights and entitlements. The national identity card is used as a breeder document for obtaining other documents such as passports, driver’s licenses and voter registration cards. The Botswana National Identity System is facilitated by legal reforms and reviews, risk management, rigorous re-engineering and re-design of business processes, an effective ID management cycle, continuous monitoring and evaluation, and data security and integrity management. It is envisaged that the ID-management system will in the future be linked to the immigration and citizenship system under the department of immigration and citizenship to progress it to a fully-fledged population register or people hub.